EFEKTIVITAS TENAGA KONTRAK PADA BADAN PERENCANAAN PEMBANGUNAN DAERAH DAN PENELITIAN PENGEMBANGAN KABUPATEN BANGGAI KEPULAUAN - Astuti, Dewi; Daswati, Daswati; Natsir, Nawawi (Katalogis, 2018)
The purpose of this study was to analyze the effectiveness of the performance of contract workers at the regional development planning agency and to research the development of Banggai Island districts. The main theories that become the reference in this resesrch are the effectiveness theory by Richard M. Steers (1980:192), in measuring the effectiveness of employee’s work includes 3 aspects: 1) adaptability; 2) work performance; 3) job satisfaction. The research method used descriptive-qualitative approach. The location of this research is in the regional development planning agency and to research the development of Banggai Island districts in the treasury division with informants amounting to 6 people who were selected purposively. The data collection was by done by means of interview, observation and documentation. The data analysis techniques used was the interactive model of Miles and Huberman. Based on the results of the results of the research, in the looking at the effectiveness of the performance of contract workers at the regional development planning agency and research on the development of Banggai Island districts can be seen from aspects, it was adaptability work performance and job satisfaction aspects, in which the overall performance of contract workers at the regional development planning agency and research on the development of Banggai Island is not yet effective.